As contribuições das tecnologias da informação e comunicação (TIC), no trabalho do coordenador pedagógico - MONTEIRO, Hérica de Fátima Carvalho (2020)
Taking into account the advances in information and communication technologies and the particularities of the work of the pedagogical coordinator, this article aims to reflect on the use of information and communication technologies (ICT) as a pedagogical tool in the work of the coordinator pedagogical. It is a bibliographical review article that has as reference authors Moran (2014), Pinto (2013) and Veloso (2011). Because it is a bibliographical review, it was chosen to reflect descriptively what each author stands in relation to the subject, presenting succinctly the attributions and functions of the pedagogical coordinator; What are information and communication technologies and how do you understand them? The relevance of ICT for pedagogical work. It is concluded that it is essential to insert information and communication technologies as facilitating resources in the work of the pedagogical coordinator.